Ethics For Managers in Corporate Governance - Ganguly, Bijoya (Prabandhan: Indian Journal of Management, 2010)
It may be appropriate to begin by saying something about the nature and meaning of ethics. Quite a few people will automatically think of ethics as providing a system of guidance based on a set of principles or rules. These rules will help us to determine what is good, bad, right or wrong. There is a good deal of truth in this perception. However, it needs to be viewed in a much broader context.